2022
DOI: 10.5195/jmla.2022.1251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adverse drug reaction formatting in drug information mobile phone applications

Abstract: Objective: To evaluate the differences in presentation (formatting) of adverse drug reaction (ADR) information within drug monographs in commonly used drug information (DI) mobile device applications. Methods: A cross-sectional analysis of ADR formatting of twenty commonly prescribed oral medications within seven DI mobile applications was performed. Databases were assessed for ADR information, including presence of placebo comparisons, severity of ADR, onset of ADR, formatting of ADRs in percentile (quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This section solicits patient agreement on the clarity, adequacy, and usefulness of discharge medication information, including side effects and warnings, employing a 0-10 scale from strongly disagree to strongly agree. The section on self-reported medication-taking behavior is developed based on the MMAS-4 (19) and relative studies (20). It includes two items: (1) whether they ever forgot to take their medication and (2) whether they ever experienced medication side effects, both measured by binary responses (Yes/No).…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…This section solicits patient agreement on the clarity, adequacy, and usefulness of discharge medication information, including side effects and warnings, employing a 0-10 scale from strongly disagree to strongly agree. The section on self-reported medication-taking behavior is developed based on the MMAS-4 (19) and relative studies (20). It includes two items: (1) whether they ever forgot to take their medication and (2) whether they ever experienced medication side effects, both measured by binary responses (Yes/No).…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…Kheshti et al 18 compared 5 drug interaction screening programs, identifying variations and deficiencies in the programs, suggesting an evaluation of interactions in two programs or more, to compare their results. McConachie et al 19 compared the formatting of the frequency of adverse reactions of 20 medications between 7 databases, showing that the formatting was different between them, due to the variation in information, such as references, severity, and other parameters that can influence clinical decisions. In our study, when comparing the databases, we also observed a difference between them, both in the number of medications with data on adjustment and dialysis and in the agreement between these databases.…”
Section: Rbfhssmentioning
confidence: 99%
“…Kheshti et al 18 compared the ability of programs to detect clinically important medication interactions and concluded that all the programs evaluated were deficient in detecting medication interactions. McConachie et al 19 compared the presentation of adverse drug reactions in medication information programs, and identified variations between them that could impact clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Eight questions were designed to measure design quality, perceived usefulness, and behavior intention using a Likert scale ranging from 0, 'strongly disagree' to 10, 'strongly agree'; Free text fields were provided to solicit provides' comments on the PDIS experiences; Demographic information was collected at the final section. The pre-post patient surveys consist of four sections: (i) The patient experience, drawn from the validated local assessment tool, the Short-form Hong Kong Inpatient Experience Questionnaire (SF-HKIEQ) (21), soliciting patient agreement on the clarity, adequacy, and usefulness of discharge medication information, including side effects and warnings, employing an ordinal scale (yes/ to some extent/ no) or Likert scale of 0-10 from strongly disagree to strongly agree; (ii) Self-reported medication-taking behavior, developed based on the MMAS-4 ( 22) and relative studies (23), asking whether they were compliant with their medication regimen and whether they ever experienced medication side effects, measured by binary responses (Yes/No); (iii) Free text field soliciting patients' comments on the PDIS experiences; (iv) Patient characteristics. The patient post-survey includes the same question of the design quality domain of the staff survey, allowing comparative analysis: the PDIS information clarity, adequacy, and usefulness.…”
Section: Data Collection Instrumentmentioning
confidence: 99%